Traditional and Non-traditional Masculine Representations in Macbeth (Shakespeare‘s and Kurzel‘s) - Montenegro Bonilla, Joseph (2018)
InterSedes: Revista Electrónica de las Sedes Regionales de la Universidad de Costa Rica